Uanauna gen. nov., a new genus of fireflies endemic to the Brazilian Atlantic forest (Coleoptera: Lampyridae), with key to brazilian genera of Lucidotina - Campello-Gonçalves, Lucas; Souto, Paula M.; Mermudes, José R.m.; Silveira, Luiz F.l. (Zootaxa, 2019)
Here, we propose Uanauna gen. nov. (Lampyridae: Photinini), a new monotypic genus of fireflies endemic to the Brazilian Atlantic Forest. Uanauna angaporan sp. nov. occurs in Submontane and Montane forest habitats at the Serra do Mar mountain range, in the Southern Fluminense region (Rio de Janeiro State, Southeastern Brazil). The new species was recorded both on the mainland, at the municipality of Itaguaí and Rio de Janeiro, and at the continental island of Ilha Grande, in Angra dos Reis, at the Rio de Janeiro State. An occurrence map and illustrations of diagnostic features are given for the new taxa, as well as a key to Lucidotina genera in Brazil.